Audiodescrição de expressões e símbolos de Cálculo Diferencial e Integral para software leitor de tela - Silva, Davi Cândido da (2024)
This research falls within the field of Translation Studies, Intersemiotic Translation and Accessible Audiovisual Translation (TAVA), within this, in the form of audio description (AD) and didactic audio description (ADD). Based on the theoretical framework of these areas and the basic notions of Differential and Integral Calculus – CDI, we aim to systematize an ADD proposal for CDI mathematical expressions and symbols for screen reader software. In order to be successful in this purpose, it was necessary to establish specific objectives: analyze the limits and possibilities of NVDA when reading the aforementioned expressions; draw up a comparison between the data found, in light of the bibliographical review on the topic and finally, develop complementary proposals that assist in the translation and access to content, corroborated by the contributions of our consultants. We can justify the contributions of this work – both in academic and social terms – as we seek to propose instruments, methods and intersemiotic translation strategies that are capable of assisting in the participation, retention and inclusion of students with visual impairments in higher education. This study has the purpose of developing means that help to make mathematical content in Higher Education accessible, through the systematization of ADDs. As for the methodology, this study is classified as descriptive, as it describes the characteristics of a phenomenon, which in this case was to analyze the limits and possibilities of the reader software, NVDA, when reading the expressions and equations of the CDI discipline with and no AD. To carry out the tasks we set out to do, it was necessary to establish a sequence of actions. Therefore, to better organize the methodological path, the research was divided into complementary stages: we submitted two materials to NVDA. Initially, the basic equations and expressions of the CDI, without the AD proposals. Then, the same mathematical notations, however, this time, accompanied by ADs and other translational strategies that helped us achieve the objectives set. It was also at this stage that we filled in the “Collection Table” with comparisons of the readings made by the software. Finally, we articulate the ADD proposals for the defining expressions of each concept. To validate the actions carried out, we were guided by the observations of AD consultants. Regarding the results obtained, we noticed that NDVA presents certain limitations for reading more complex expressions and sometimes even simple ones. The suggested options for making the content accessible were well accepted by the consultants. The importance of other tools, combined with ADD, to make the content of the disciplines accessible was also verified, since in a teleological reflection it does not intend to obliterate other methods, techniques, technologies and strategies, but just the opposite, weadmit and suggest the possibility and need for resources that can expand and complement access to content.